A Novel Video Steganography Algorithm Based on Trailing Coecients for H.264/AVC - Zhang, Yingnan; Zhang, Minqing; Wang, Xu An; Niu, Ke; Liu, Jia (Informatica, 2015)
Accompany with the growth of the speed in network, people’s living standard has greatly improved, but the threaten to its information security has also appeared, as an important branch of information security, steganography is a useful method to protect the secret information safety. In view of the high complexity of current video steganographic algorithms, and combining with the trailing coefficient produced in the process of quantization of H.264 encoding standard, we put forward a kind of algorithm based on trailing coefficients. The algorithm firstly conduct DCT transform on the frame, then obtain the trailing coefficient for each quantized DCT blocks, last, embedding by changing its values. The experimental result indicates that: this algorithm has little influence on video quality and has large capacity of steganography, and has a strong anti-steganalysis capability, high robustness. Above all, the information security has been protected.